Setting partnership for climate change adaptation in the CCAFS Yatenga site, Burkina Faso: analysis of gaps and opportunities - Jacques S; Zougmoré, Robert B.; Sawadogo, I.; Bationo, B. André; Partey, Samuel T. (2016)
This paper analyzes patterns of social interaction within the organizations working in the Yatenga province of Burkina Faso, and develops purposive partnership framework that can facilitate the scaling up of the action research outputs and outcomes. A diagnostic tool for evaluating group functioning was used to elucidate the current situation of partnership development in this province. Further, partnership and networking was analyzed using the network density which describes the portion of the potential connections in a network of organizations that are actual connections. The results suggest that the desired partnership as requested/expected by stakeholders is far from working as it could be. The stakeholders therefore agreed that network density need to be increased for future partnership, with clearly defined vision, shared responsibilities in generating knowledge and results, and capacities to monitor, evaluate and communicate on the program impacts. For this purpose, future partnership need to combine scale-based and competency-based frameworks to be beneficial at scale and pulling together organizations’ competencies. Implementing both frameworks would lead to an effective partnership on climate change adaptation in agriculture and food security. However, the successful development of this purposive partnership will require capacity development for the group of partnering organizations.